Antioxidant, antimicrobial and neuroprotective effects of Octaviania asterosperma in vitro. Issue 2 (3rd April 2021) - Sevindik, Mustafa; Akgul, Hasan; Selamoglu, Zeliha; Braidy, Nady
ABSTRACT: Octaviania asterosperma: (hypogeous Basidiomycota) We investigated the phenolic composition, and antioxidant, antimicrobial and antigenotoxic effects of methanol extracts of fruiting bodies from Octaviania asterosperma. The total phenolic content (ppm) of O. asterosperma was found to be catechin (54.73 ± 4.68), epicatechin (123.90 ± 8.52), caffeic acid (4.23 ± 0.97), p-hydroxybenzoic acid (37.72 ± 3.84), cinnamic acid (58.07 ± 5.40), gallic acid (56.64 ± 6.39), clorogenic acid (80.76 ± 4.92) and coumaric acid (2.45 ± 0.15). The total antioxidant status (TAS), total oxidant status (TOS) and oxidative stress index (OSI) were 3.410 ± 0.099 mmol/L, 7.548 ± 0.147 μmol/L and 0.221 ± 0.005 respectively. O. asterosperma showed some promising antimicrobial activity. The extract showed no genotoxic potential and attenuated hydrogen peroxide (H2O2)-induced oxidative DNA damage in neurons. Pre-treatment with O. asterosperma maintained mitochondrial function, reduced expression levels of cleaved-caspase-3 and apoptosis-inducing factor (AIF) when HT22 cells were exposed to pathophysiological concentrations of GLU (25 mM) and modulated protein kinase B (Akt), the mammalian target of rapamycin (mTOR), and the phosphotase and tensin homolog on chromosome ten (PTEN). O. asterosperma is an important food for the treatment or management of neurodegenerative disorders due to its phenolic content and potent antioxidant and anti-excitotoxic effects.